Idaman Bridal House; Wedding Packages / Rozalia Mohamad Zain ... [et al.] - Abd hamid, Noor hazrina; Syed Mohd Azni, Sharifah Intan Farini; Jamaludin, Duratul Ai’in; Mohamad Zain, Rozalia; Abdul Rahman, Noor Hafiza (2001)
Idaman Bridal House is a business that provides a wedding package. Their services are included rental wedding suits, dais decoration, bridal bedroom decoration, goodies, ‘bunga telur’ and potpourri. The business is situated at Shahab Perdana Bus terminal, alor setar kedah.